Pengaruh Insentif Terhadap Kinerja Karyawan Pada Perusahaan - Rizka Della Cahyani; Yufita Sri Rejeki; Kezia Abigail Sousia; Sekar Arum Larasati; Angelina Putri Rahayu; Saridawati Saridawati (Journal Economic Excellence Ibnu Sina, 2024)
Intensive compensation for employees is an achievement that is in conflict with the use of energy or compensation for services performed by the workforce. By paying employees, they will gain financial and non-financial benefits, compensation will encourage employees to analyze their work well so that their skills improve. The higher the salary a company offers its employees, the greater the employee's efforts to improve their performance. Compensation is an important thing that companies must provide fairly to their employees, both financial and non-financial. Employees need to be given compensation such as bonuses, allowances, a comfortable working environment, and work that can demonstrate their abilities so that the employee can provide the best results for the company. One of the aims of this research is to determine the effect of financial compensation on employee performance. The success achieved by a company cannot be separated from the important role of the human resources department. Therefore, the company is committed to developing a highly skilled workforce who has the agility and mindset to continue to develop and appreciate the company's values, to lead the business in the context of industrial development, to evaluate employee performance based on respondents' perceptions independently. This is done by a company with the aim of maintaining good service quality at this time, by evaluating it based on employee perceptions..